2017
DOI: 10.1111/jre.12493
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different mouse strains to peri‐implantitis

Abstract: Background and Objective Peri‐implantitis (PI) is an inflammatory condition that affects the tissues surrounding dental implants. Although the pathogenesis of PI is not fully understood, evidence suggests that the etiology is multifactorial and may include a genetic component. The aim of this study was to investigate the role of genetics in the development of peri‐implantitis. Material and Methods Four‐week‐old C57BL/6J, C3H/HeJ and A/J male mice had their left maxillary molars extracted. Implants were placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In the present study, a murine model of bone absorption induced by titanium particles was used to illustrate the molecular mechanisms involved in initiation and progression of peri‐implant bone loss instead of a canine model. Recently, rodent animal models have been developed increasingly on account of substantial genomic, transcriptomic, and proteomic tools available for insights into molecular and cellar events around oral implants similar to humans . It has been reported that titanium particle sizes, amount and duration of implantation have impact on the extent of inflammation response which is required for triggering bone osteolysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a murine model of bone absorption induced by titanium particles was used to illustrate the molecular mechanisms involved in initiation and progression of peri‐implant bone loss instead of a canine model. Recently, rodent animal models have been developed increasingly on account of substantial genomic, transcriptomic, and proteomic tools available for insights into molecular and cellar events around oral implants similar to humans . It has been reported that titanium particle sizes, amount and duration of implantation have impact on the extent of inflammation response which is required for triggering bone osteolysis .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rodent animal models have been developed increasingly on account of substantial genomic, transcriptomic, and proteomic tools available for insights into molecular and cellar events around oral implants similar to humans. [32][33][34] It has been reported that titanium particle sizes, amount and duration of implantation have impact on the extent of inflammation response which is required for triggering bone osteolysis. 35 Therefore, on referring to titanium particle-induced mouse calvarial osteolysis model, 23 20 mg Ti particles with a mean particle size of 3.32 ± 2.39 μm were applied to trigger local aseptic inflammatory response of peri-implant tissue.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Paralleling clinical observations of periodontal disease, histological and molecular analysis of experimental animal models of periodontitis in mice and rats have provided important insights into the disease pathogenesis recapitulating clinical, radiographic, and histologic features of the disease (de Aquino et al, ; de Molon et al, ; de Molon, Mascarenhas, et al, ; Graves, Fine, Teng, Van Dyke, & Hajishengallis, ; Hiyari et al, ; Hiyari et al, ; Li & Amar, ; Polak et al, ; Polak, Shapira, Weiss, & Houri‐Haddad, ; Saadi‐Thiers et al, ; Wilensky, Gabet, Yumoto, Houri‐Haddad, & Shapira, ). Moreover, animal models with physiological complications have been extensively utilized to develop new treatment modalities with more effective therapeutic strategies, inquiry host–pathogen interactions, study the effects of surgical interventions, and evaluate the intrinsic effects of periodontal infection or inflammation on systemic conditions (de Molon, de Avila, et al, ; de Molon, de Avila, & Cirelli, ; de Molon, Mascarenhas, et al, ; Graves et al, ; Graves, Kang, Andriankaja, Wada, & Rossa Jr., ; Matsuda et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that sTREM-1 is generated through the proteolytic cleavage of mature cell- surface-anchored TREM-1 by MMP [ 13 , 14 ], the reduction in MMP-8 might have reduced the amount of available sTREM in the intracellular area. Since it is known that MMP-8 is related to bone loss [ 40 , 41 ], we speculate that is the reason why the reduction in MMP-8 had a direct impact on sTREM levels in the PI group but not in the MU group. While TREM-1 is an important modulator of the inflammatory response and is also shed by the membranes of activated phagocytes being found in its soluble form (sTREM-1) in saliva and gingival crevicular fluid, the reduction in the expression of sTREM-1 has clinical applications to the pathogenesis of the peri-implant disease.…”
Section: Discussionmentioning
confidence: 94%